Billet shape optimization for minimum forging load - Jolgaf, Mohamed A. Abdulmawlla; Sulaiman, Shamsuddin; Mohd Ariffin, Mohd Khairol Anuar; Abdul Aziz, Faieza (EuroJournals Publishing, 2008)
The objective of this paper is to obtain an optimal billet shape in the consideration of the influence of the metal flow deformation in closed die forging process. Finite element method in conjunction with optimization algorithm was used to analyze the effect of billet shape on forging load in axisymmetric closed die forging process. Finite element software (ANSYS) was used to simulate closed die forging process and then performing a series of optimization iterations in order to obtain the optimal shape of the billet based on forging load minimization. The material used is aluminium metal matrix composite (AlMgSi matrix with 15% SiC particles). The goal of the simulation and optimization process is to minimize the forging load and produce crack-free forgings. The optimal shape of the billet that gives minimum forging load was obtained after several optimization iterations. The approach used in this study could be extended to the optimization of more complicated forging products.